The Establishment of Expanded Newborn Screening in Rural Areas of a Developing Country: A Model from Health Regions 7 and 8 in Thailand - Khunton Wichajarn; Nopporn Sawatjui; Prinya Prasongdee; Amrin Panklin; Kanda Sornkayasit; Natchita Chungkanchana; Supharada Tessiri; Preawwalee Wintachai; Sumalai Dechyotin; Chalanda Pasomboon; Jilawaporn Ratanapontee; Sureerat Thanakitsuwan; et al. (International Journal of Neonatal Screening)
Expanded newborn screening (NBS) programs are essential for early detection and treatment. This study highlights the implementation of an expanded NBS program for inborn errors of metabolism (IEMs) and congenital hypothyroidism (CH) in rural Thailand, focusing on Health Regions 7 and 8 as a model for resource-limited settings. Using the KKU-IEM web-based platform, the program streamlined workflows, integrating logistics, real-time sample tracking, and electronic data management. Regular training sessions, continuous feedback, and systematic monitoring improved outcomes. Starting from October 2022, the program covered 98.6% of 123,692 live births, identifying 101 CH cases (1 in 1208 live births) and 20 IEM cases (1 in 6100 live births). The CH incidence was slightly higher than Thailand’s national average, while the IEM incidence was double that found in a previous Bangkok pilot study. Six cases highlighted maternal conditions affecting outcomes. Process improvements reduced the average reporting time from 9.13 days in 2023 to 8.4 days in 2024, with a 19% reduction in Bueng Kan Province. Efficiencies were driven by electronic ordering, real-time tracking, and stakeholder collaboration. This program demonstrates a scalable model for rural settings, emphasizing technology integration, collaboration, and quality control. Future efforts should refine diagnostics, expand disease coverage, and enhance long-term outcomes.